2013
DOI: 10.1088/1367-2630/15/1/015026
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved studies on the collapse of magnesium atom foam in helium nanodroplets

Abstract: Magnesium atoms embedded in superfluid helium nanodroplets have been identified to arrange themselves in a metastable network, referred to as foam. In order to investigate the ionization dynamics of this unique structure with respect to a possible light-induced collapse, the femtosecond dual-pulse spectroscopy technique is applied. Around zero optical delay a strong feature is obtained which represents a direct probe of the foam response. We found that upon collapse, ionization is reduced. A particular intensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…However, we speculate that larger organic molecules, for which the change in electronic and molecular structure upon electronic excitation is weaker and therefore vibronic spectra are less perturbed [14], may still exhibit vibronic dynamics on time scales accessible to fs spectroscopy, similar to molecules embedded in heavier rare gas matrices [157]. Apart from these studies by our group, only Mg-doped He nanodroplets have been studied by fs spectroscopy in the group of K.-H. Meiwes-Broer, J. Tiggesbäumker in Rostock [109,158]. Based on linear absorption spectra and on fs REMPI transients of multiply doped He droplets, it was concluded that Mg atoms aggregate in He nanodroplets in an unusual way to form a foam-like structure where the metal atoms arrange themselves in a regular 10Å-spaced network separated by He atoms.…”
Section: Time-resolved Photoionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we speculate that larger organic molecules, for which the change in electronic and molecular structure upon electronic excitation is weaker and therefore vibronic spectra are less perturbed [14], may still exhibit vibronic dynamics on time scales accessible to fs spectroscopy, similar to molecules embedded in heavier rare gas matrices [157]. Apart from these studies by our group, only Mg-doped He nanodroplets have been studied by fs spectroscopy in the group of K.-H. Meiwes-Broer, J. Tiggesbäumker in Rostock [109,158]. Based on linear absorption spectra and on fs REMPI transients of multiply doped He droplets, it was concluded that Mg atoms aggregate in He nanodroplets in an unusual way to form a foam-like structure where the metal atoms arrange themselves in a regular 10Å-spaced network separated by He atoms.…”
Section: Time-resolved Photoionizationmentioning
confidence: 99%
“…These cluster mass progressions can extended out to masses of thousands of dopant monomers, in particular when the binding of the neutral cluster is weak thereby causing only little shrinkage of the He droplets due to cluster aggregation [107][108][109]. Therefore, small Ak metal clusters are presumably formed in weakly bound high-spin configurations, whereas large clusters observed in mass spectra of heavily doped large He droplets are assumed to be metallic [69,91,110].…”
Section: Photoion Mass Spectramentioning
confidence: 99%
“…[2][3][4][5][6][7] Still, not only do the droplets provide new ways for synthesis but the products also provide new insight into properties of helium droplets. For example, the shape of silver aggregates grown in very large droplets reflects the presence of quantized vortices in superfluid droplets.…”
mentioning
confidence: 99%
“…In the ultimate case multiple particle doping may thus produce numerous individual particles inside one helium droplet shielded from each other by a helium solvation layer. In contrast to the formation of a large cluster inside the helium droplet this phenomenon is addressed as foam (Przystawik et al, 2008; Goede et al, 2013). …”
Section: Discussionmentioning
confidence: 99%